2020
DOI: 10.18662/rrem/12.3/321
|View full text |Cite
|
Sign up to set email alerts
|

Fairy-Tale Therapy as a Means of Forming Health- Saving Competence of Children with SEN

Abstract: The article is devoted to defining the peculiarities of forming health-saving competence of children, including the ones with special educational needs, by fairytale therapy means. The objective of the study is to highlight the specific way in which the health-saving competence of children, including the ones with SEN, can be formed by means of fairy-tale therapy. Results: A list of fairy tales, works of children's literature, poems, cartoons and films was identified. Examples of activities for children using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…According to Heri Rahyubi (2022); Amorós et al, 2018), if the environment where children grow and develop supports children to move freely, then motor development, especially in early childhood, will be more ideal. In his research, Aini (in Kazachiner & Tkachenko, 2020) found that children's locomotor movements, especially toe walking and jumping, were strongly influenced by the imagination of gymnastics. Fantasy gymnastics can help with when children's basic movement skills are fully developed, they will be more interested in applying their imagination in the form of gymnastic exercises (Kiranida, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…According to Heri Rahyubi (2022); Amorós et al, 2018), if the environment where children grow and develop supports children to move freely, then motor development, especially in early childhood, will be more ideal. In his research, Aini (in Kazachiner & Tkachenko, 2020) found that children's locomotor movements, especially toe walking and jumping, were strongly influenced by the imagination of gymnastics. Fantasy gymnastics can help with when children's basic movement skills are fully developed, they will be more interested in applying their imagination in the form of gymnastic exercises (Kiranida, 2019).…”
Section: Introductionmentioning
confidence: 99%